2009
DOI: 10.1021/ma901829d
|View full text |Cite
|
Sign up to set email alerts
|

Regioregular Poly(3-pentylthiophene): Synthesis, Self-Assembly of Nanowires, High-Mobility Field-Effect Transistors, and Efficient Photovoltaic Cells

Abstract: We report the synthesis, characterization, solution-phase assembly of nanowires, field-effect charge transport, and photovoltaic properties of regioregular poly(3-pentylthiophene) (P3PT), the first regioregular poly(3-alkylthiophene) with an odd-numbered alkyl side chain length to be so investigated. Two samples of P3PT with weight-average molecular weights of 61 800 and 77 000 and 1.4−1.5 polydispersity index have comparable solubility and processability in organic solvents as regioregular poly(3-hexylthiophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(140 citation statements)
references
References 64 publications
12
128
0
Order By: Relevance
“…The melting transition of the P3HT block in the block copolymers increases from 214 C in HcH63 to 220 C in HcH77, which is lower than 240-245 C observed in the homopolymer P3HT. 28,47 Similarly, the melting transition of the P3cHT block in the block copolymers decreases from 363 C in HcH63 to 310 C in HcH77, which is lower than 386 C seen in the P3cHT homopolymer. The increase of the T m of each block with increasing amount of that block in the HcH diblock copolymer can be understood in terms of effects of molecular weight and purity on melting transition.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The melting transition of the P3HT block in the block copolymers increases from 214 C in HcH63 to 220 C in HcH77, which is lower than 240-245 C observed in the homopolymer P3HT. 28,47 Similarly, the melting transition of the P3cHT block in the block copolymers decreases from 363 C in HcH63 to 310 C in HcH77, which is lower than 386 C seen in the P3cHT homopolymer. The increase of the T m of each block with increasing amount of that block in the HcH diblock copolymer can be understood in terms of effects of molecular weight and purity on melting transition.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that the molecular weight significantly affects the hole mobility in P3HT thin films. 47,55,56 Longer polymer chains have more chances of interconnection between highly organized domains, and hence give higher charge-carrier mobility.…”
Section: Field-effect Transistorsmentioning
confidence: 99%
“…25 The high hole mobility of P3HT nanowires is attractive for organic PVs, especially when combined with electron carriers, such as fullerenes. PV devices having active layers fabricated from solutionassembled poly(3-alkyl thiophene) nanowires display power conversion efficiency (PCE) values comparable with optimized devices that require annealing of P3HT/fullerene films; 15,19,26,27 for example, blending phenyl C 61 Àbutyric acid methyl ester (PC 60 BM) with P3HT fibrils gave devices with a 3.9% PCE, significantly higher than that obtained for thin films of noncrystallized P3HT and PC 60 BM (1.1%), and on par with annealed thin films (3.7%). 28 Active layers prepared by deposition of solution-prepared fibrils do not suffer from the vertical phase separation of the polymer and fullerene components, as observed during thermal annealing of conventional thin films.…”
Section: Nanoscale Assembly T Emrick and E Pentzermentioning
confidence: 99%
“…Obtaining high molecular weights and low polydispersities appears to be crucial for improving device performance [75]. In order to establish the required stoichiometries for optimized polycondensations, pure crystalline stannyl or boronate components are needed, but further aspects such as the acceleration of the reactions by microwave irradiation instead of conventional heating [76,77], appropriate choice of the catalytic metal-ligand complex [48,78,79], end-capping to remove undesirable terminal functional groups [80][81][82][83][84][85], and rigorous purification of the products could well be added to this list of improvements. Morphological control of conjugated polymers [86,87], for example, in designing bulk heterojunction solar cells [58][59][60][61]70], has demanded the synthesis of rod-rod and rod-coil block copolymers and, in this context, chain-growth mechanisms involving the living ends of the rod-like segments have become particularly important [81,[88][89][90][91].…”
Section: Expanding Synthetic Chemistry To Complex Macromoleculesmentioning
confidence: 99%